Case Report: A Homozygous Mutation (p.Y62X) of Phospholipase D3 May Lead to a New Leukoencephalopathy Syndrome - Liu, Yi-Hui; Zhang, Hai-Feng; Jin, Jie-Yuan; Wei, Yan-Qiu; Wang, Chen-Yu; Fan, Liang-Liang; Liu, Lv (Frontiers in Aging Neuroscience, 2021)
Leukodystrophies are a heterogeneous group of inherited disorders with highly variable clinical manifestations and pathogenetic backgrounds. At present, variants in more than 20 genes have been described and may be responsible for different types of leukodystrophies. Members of the phospholipase D family of enzymes catalyze the hydrolysis of membrane phospholipids. Meanwhile, phospholipase D3 (PLD3) has also been found to exhibit ssDNA acid 5′ exonuclease activity. Variants in phospholipase D3 (PLD3) may increase the risk of Alzheimer's disease and spinocerebellar ataxia but this hypothesis has not been fully confirmed. In this study, we identified a novel homozygous mutation (NM_012268.3: c.186C>G/ p.Y62X) of PLD3 in a consanguineous family with white matter lesions, hearing and vision loss, and kidney disease by whole exome sequencing. Real-time PCR revealed that the novel mutation may lead to nonsense-mediated mRNA decay. This may be the first case report on the homozygous mutation of PLD3 in patients worldwide. Our studies indicated that homozygous mutation of PLD3 may result in a novel leukoencephalopathy syndrome with white matter lesions, hearing and vision loss, and kidney disease.